2015
DOI: 10.1371/journal.pgen.1005749
|View full text |Cite
|
Sign up to set email alerts
|

The Mammalian Orthologs of Drosophila Lgd, CC2D1A and CC2D1B, Function in the Endocytic Pathway, but Their Individual Loss of Function Does Not Affect Notch Signalling

Abstract: CC2D1A and CC2D1B belong to the evolutionary conserved Lgd protein family with members in all multi-cellular animals. Several functions such as centrosomal cleavage, involvement in signalling pathways, immune response and synapse maturation have been described for CC2D1A. Moreover, the Drosophila melanogaster ortholog Lgd was shown to be involved in the endosomal trafficking of the Notch receptor and other transmembrane receptors and physically interacts with the ESCRT-III component Shrub/CHMP4. To determine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 65 publications
5
39
1
Order By: Relevance
“…Moreover, a single interaction-competent DM14 repeat is sufficient for rescue of the lgd null phenotype in vivo . The binding mode between Shrub and Lgd appears to be conserved in humans, as CC2D1A/Lgd2 and CC2D1B/Lgd1 can rescue lgd mutants in a shrb dependent manner (Drusenheimer et al, 2015) and charge reversal of the acidic face of CHMP4B, the mammalian homolog of Shrub, also disrupts interaction with human Lgd2/CC2D1A (Martinelli et al, 2012). In yeast, where the ESCRT pathway has been extensively defined, an Lgd ortholog appears to be lacking, suggesting that Lgd serves a regulatory role, as opposed to an obligate function in polymer assembly and ESCRT activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a single interaction-competent DM14 repeat is sufficient for rescue of the lgd null phenotype in vivo . The binding mode between Shrub and Lgd appears to be conserved in humans, as CC2D1A/Lgd2 and CC2D1B/Lgd1 can rescue lgd mutants in a shrb dependent manner (Drusenheimer et al, 2015) and charge reversal of the acidic face of CHMP4B, the mammalian homolog of Shrub, also disrupts interaction with human Lgd2/CC2D1A (Martinelli et al, 2012). In yeast, where the ESCRT pathway has been extensively defined, an Lgd ortholog appears to be lacking, suggesting that Lgd serves a regulatory role, as opposed to an obligate function in polymer assembly and ESCRT activity.…”
Section: Discussionmentioning
confidence: 99%
“…In animals, proper ESCRT-III function requires modulation of Shrub activity by the large multi-domain protein called Lethal (2) giant discs (Lgd) in flies, or Coiled-Coil and C2 Domain Containing proteins 1A and 1B (CC2D1A and B) in mammals (Drusenheimer et al, 2015; Troost et al, 2012). Loss of Lgd in flies results in aberrant sorting and signalling of membrane proteins such as Notch (Jaekel and Klein, 2006; Klein, 2003; Schneider et al, 2013), and produces defects in cell division (Matias et al, 2015; Morawa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These helical hairpins again pack side to side, recapitulating the intermolecular hairpin stacking interactions seen in the open CHMP1B strand. Importantly, CHMP4 filament formation can be blocked by Lgd (CC2D1A/B), a negative regulator of the multivesicular body (MVB) pathway (Drusenheimer et al 2015, Martinelli et al 2012, Troost et al 2012, Usami et al 2012), and a recent crystal structure has shown how the third DM14 domain of Lgd binds the isolated Shrub hairpin to occlude polymerization sterically (McMillan et al 2017). Thus, the similarity of open subunit structures and interactions seen in the different ESCRT-III filaments, as well as the conserved mechanisms of the Lgd (CCD1) inhibitors (Martinelli et al 2012, McMillan et al 2017), indicate broad evolutionary conservation of the opening, polymerization, and regulatory mechanisms (McCullough et al 2015, McMillan et al 2016, Tang et al 2015).…”
Section: Escrt-iiimentioning
confidence: 99%
“…In Drosophila , where only one CC2D1 homolog, lethal giant discs lgd , is present, removal of lgd is lethal during the larval stage ( Gallagher and Knoblich, 2006 ; Jaekel and Klein, 2006 ). Expression of either human CC2D1A or CC2D1B can rescue the phenotypes observed in Drosophila ( Drusenheimer et al, 2015 ), suggesting that CC2D1A and CC2D1B act redundantly. Despite wide expression of CC2D1A and its binding to multiple proteins involved in the immune response ( Chang et al, 2011 ; Chen et al, 2012 ), CC2D1A LOF in humans appears to only affect the brain, leading to a spectrum of behavioral deficits.…”
Section: Introductionmentioning
confidence: 99%